1991
DOI: 10.1002/j.1552-4604.1991.tb03739.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum/Saliva Correlations for Theophylline in Asthmatics

Abstract: Theophylline levels in mixed saliva (both stimulated and unstimulated) were compared with total and free (unbound) serum theophylline levels in 28 asthmatic outpatients using theophylline regularly. Stimulated saliva predicted both total and unbound serum theophylline concentrations within +/- 1 microgram/mL in 62.5% and 92.9%, respectively, of the samples examined. In addition, the total serum levels could be used to predict unbound serum concentrations to within +/- 1 mg/L in 100% of the cases that were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Saliva pH and saliva protein binding were not considered to be significant influences on observed variability 74 and the saliva to free plasma drug approached unity 75 . Several studies attempting to develop correlation equations to predict plasma levels from oral fluid measurement of drug concentrations have been able to predict plasma levels within 2 μg/mL 76–78 . Precision was better for the saliva to free plasma theophylline.…”
Section: Saliva Therapeutic Drug Management Applied To Drug Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva pH and saliva protein binding were not considered to be significant influences on observed variability 74 and the saliva to free plasma drug approached unity 75 . Several studies attempting to develop correlation equations to predict plasma levels from oral fluid measurement of drug concentrations have been able to predict plasma levels within 2 μg/mL 76–78 . Precision was better for the saliva to free plasma theophylline.…”
Section: Saliva Therapeutic Drug Management Applied To Drug Classesmentioning
confidence: 99%
“…75 Several studies attempting to develop correlation equations to predict plasma levels from oral fluid measurement of drug concentrations have been able to predict plasma levels within 2 g/mL. [76][77][78] Precision was better for the saliva to free plasma theophylline. Others found that stimulated saliva samples improved the correlation sufficiently between saliva and free fraction in serum so that saliva-based predictions of theophylline levels could be made in adults with asthma 74 or with chronic airflow obstruction.…”
Section: Bronchodilators-theophyllinementioning
confidence: 99%
“…Many later studies support the conclusions that the CsaJ/Cup exhibits acceptable variability, pH and concentration independence and a high degree of utility for predicting Cup (Blanchard et al 1991;Ebden et al 1985;Siegel et al 1990;Stoehr et al 1986). The data from these studies are summarised in table II.…”
Section: Theophyllinementioning
confidence: 67%